PATH-44. AN UNUSUAL PRESENTATION OF A PEDIATRIC MIDLINE H3K27M-MUTANT TUMOR WITH DISSEMINATED CRANIOSPINAL LEPTOMENINGEAL DISEASE. (9th November 2020) - Navarro, Ralph; Golub, Danielle; Hill, Travis; McQuinn, Michelle; Kim, Nora; Tang, Karen; Livingston, Stephanie; Cooper, Benjamin; Gardner, Sharon; Nicolaides, Theodore; William, Christopher; Zagzag, David; et al.
Abstract: BACKGROUND: H3K27M-mutant midline lesions were recently reclassified by the WHO as "Diffuse Midline Glioma" (DMG) based on their molecular signature. DMG is one of the most common and most lethal pediatric brain tumors; terminal progression is typically caused by local progression or secondary leptomeningeal dissemination. H3K27M mutations have also been infrequently associated with a histologically diverse set of lesions, particularly spinal masses with early leptomeningeal spread, but the role of H3K27M in these atypical lesions remains poorly understood. CASE PRESENTATION: A 15-year-old girl was found to have a T2/FLAIR-hyperintense and heterogeneously contrast-enhancing thalamic mass accompanied by severe leptomeningeal enhancement along the entire neuraxis. Initial infectious workup was negative, and open intracranial biopsy was inconclusive. Follow-up spinal arachnoid biopsy was diagnostic for H3K27M neuroepithelial tumor, thereafter classified as DMG. Biopsy also showed focal p53 immunopositivity, variable immunoreactivity for GFAP and synaptophysin, and an increased proliferation index, altogether suggestive of a glioneuronal origin. She received craniospinal irradiation (CSI) to 41.4Gy with a boost to the thalamic lesion to 54Gy. Imaging 1-month post-radiation demonstrated significant treatment response only with residual enhancement at the conus. CONCLUSIONS: This case report describes the unique presentation of an H3K27M-mutant midline lesion with significant craniospinal leptomeningeal spread on admission and atypical glioneuronal histopathological markers. Given her avid leptomeningeal disease, spinal dural biopsy could have been considered earlier given its diagnostic yield in classifying the lesion as DMG. This lesion, however, additionally demonstrated synaptophysin positivity. Per extensive literature review, this histopathology is also potentially consistent with diffuse leptomeningeal glioneuronal tumor (DLGNT). This patient's uniquely marked treatment response to CSI is also not typically observed in DMG, further supporting the possibility of an alternative molecular identity. In atypical DMG cases, particularly with early leptomeningeal spread, additional consideration of clinical and histopathological context is warranted for accurate diagnosis and prognostication.